ADHOCRACY CULTURE, ETHICAL CULTURE, AND JOB ENGAGEMENT AMONG PRIVATE SECONDARY SCHOOL TEACHERS IN LAGOS STATE, NIGERIA (Journal of Association of Educational Management and Policy Practitioners, 2024)
This study investigated the influence of adhocracy culture, ethical culture, and job engagement among private secondary school teachers in Lagos State. Job engagement plays a pivotal role in motivating and improving teacher performance, thereby being determined by adhocracy culture and ethical culture. The study raised three research objectives, questions and formulated two null hypotheses. The study reviewed literature conceptually, empirically and theoretically. A descriptive survey research design was used, and data was collected from a sample of private secondary school teachers in Lagos State. The study encompassed a population of 18,473 teachers from 178 private secondary schools across the state. To ensure adequate representation, 400 participants were selected using stratified random sampling from six education districts in Lagos State. Structured questionnaire titled: Adhocracy Culture, Ethical Culture, and Job Engagement Questionnaire, was used as data collection instruments. Face and content validity, as well as test-retest reliability technique were used for the study. Mean and standard deviation were used to answer the research questions. The hypotheses were tested using Chi-Square (X2) statistics at 0.05 alpha level. The findings of the study showed there are positive influence of adhocracy culture, and ethical culture on job engagement of private secondary school teachers in Lagos State. Based on the findings, the study recommended that school administrators should actively foster an adhocracy culture within their institutions by encouraging innovation, creativity, and risk-taking among teachers, and schools should prioritize the development of an ethical culture that emphasizes integrity, honesty, and fairness.